Collaboration in Digitising Cultural Heritage as a strategy to sustain access and sharing of cultural heritage information in Uganda - Kaddu, Sarah (My University, 2015)
Uganda has little of its cultural heritage within its boundaries. This is partly because of lack of systematic preservation, conservation and restoration of the Uganda cultural heritage. Worse still many of the cultural artifacts were exported by colonial masters while others were destroyed by natural disasters including fire, war and malicious ignorant people. Consequently, collaborative efforts within the country and outside the country must be taken to re-possess or find means to make basic research on cultural heritage to reinvigorate it. This would need collaboration within Uganda and outside Uganda. Consequently, digitization of cultural heritage has taken popular turn in Uganda as elsewhere in the world as a means of conservation and preservation of cultural heritage for posterity. Through cooperation between World Digital Library (WDL) and the National Library of Uganda (NLU) remarkable digitization of Uganda Cultural heritage has taken place. The aim of this research was to identify viable collaboration within and outside Uganda on digitisation of Uganda’s cultural heritage. The objectives that guided this research were to: establish the objectives of World Digital Library (WDL U) in Uganda, identify the custodians and producers of Uganda’s cultural heritage, identify cultural heritage materials collected, identify collaborative partners to ensure digitisation of Uganda’s cultural heritage, establish NLU collaborative efforts available in Uganda and outside Uganda to ensure access to and digitisation of cultural heritage, to identify benefits of digitizing Uganda’s cultural heritage, and to examine the challenges in collaboration towards preserving Uganda’s cultural heritage. Methodology included: literature review on Uganda cultural heritage, study tours to custodial institutions of Uganda’s cultural heritage, interviews with staff at NLU and with individual custodians of Uganda’s cultural heritage, collaborative work with the World Digital Library. Beneficiaries will include both local and foreign, producers and consumers of Uganda cultural heritage, WDL and NLU partners/collaborators, students, researchers and posterity.